Micronutrient Supplementation and Its Association with Prevention of Postpartum Blues and Breastfeeding Outcomes: A Prospective Cohort Study in Balikpapan City - Grace Carol Sipasulta; Endah Wijayanti; Rus Andraini; Genevieva Esmeraldine Tanihatu (Poltekkes Kemenkes Palu, 2026)
Background: Postpartum blues affects 37–67% of Indonesian mothers, yet the role of micronutrient supplementation as a preventive strategy remains underexplored. This study examined whether postpartum micronutrient supplementation was associated with lower incidence of postpartum blues and improved breastfeeding outcomes among postpartum mothers in Balikpapan, Indonesia. Methods: A prospective cohort study followed 152 postpartum mothers at RS Sayang Ibu and PBM Griya Bunda Sehat, Balikpapan City, for 16 months. The exposed group (n=83) received micronutrient supplementation for six months postpartum, while the unexposed group (n=69) did not. Outcomes were assessed using the Edinburgh Postnatal Depression Scale (EPDS) and 10 Steps to Successful Breastfeeding checklist. Ethical approval was obtained (DP.04.03/7.1/07893/2023). Results: Among supplemented mothers, 89.2% experienced no postpartum blues compared with 66.7% in the non-supplemented group. Micronutrient supplementation was significantly associated with reduced postpartum blues risk (p=0.001; OR=0.243; 95%CI: 0.10–0.57). Supplementation was also associated with improved breastfeeding success (p=0.030; OR=0.433; 95%CI: 0.20–0.93), with 83.1% achieving successful breastfeeding. Conclusion: Postpartum micronutrient supplementation was significantly associated with lower risk of postpartum blues and better breastfeeding outcomes. These findings suggest the potential benefit of integrating supplementation into maternal health programs, in line with SDG targets 3.1 and 3.4, pending confirmation through randomized controlled trials.